A tale of three cities: the concept of smart sustainable cities for the Arctic. (2nd January 2020) - Raspotnik, Andreas; Grønning, Ragnhild; Herrmann, Victoria
ABSTRACT: This article considers established metrics for smart city development and evaluates their suitability for implementation in Arctic urban settlements. To do this, the article first surveys smart city literature and the standardization of 'smartness' metrics, with particular interest in the International Standards Organization's (ISO) categorization efforts. It then proposes a northern framework of measurement to evaluate smart cities that adjusts smart metrics from current non-Arctic scholarship to the relatively low populations, peripheral development, remote locations, and harsh climate conditions of the circumpolar north. To test this argument of a new smart framework, the article moves to examine the strategies of three circumpolar cities at different points of smart development: Anchorage (United States), Bodø (Norway) and Oulu (Finland). The article concludes by identifying areas of success and shortcomings for each city analyzed. Smart cities can be a crucial step towards a sustainable future in the circumpolar north, contributing to a 'smarter' approach to economic, social, and environmental development. Exploring this is important because these frameworks have implications for how policymakers in northern regions choose to plan and implement their city strategies.